MINAT DAN KUALITAS PELAYANAN TERHADAP TINGKAT KUNJUNGAN KE PERPUSTAKAAN - Sumiati, Eti (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2019)
This study aims to determine the interest and quality of service to visit level in the library IPDN Jatinangor. The result of the research shows that the interest and the quality of service have partial and simultaneous effect on visit level in the library of IPDN Jatinangor. Where, member interest variable and service quality together have influence equal to 51,80% to visit level of library of IPDN Jatinangor.